ANALISIS CYBERSICKNESS PADA PERMAINAN BEAT SABER VIRTUAL REALITY DI GAME BLINK PLAYSTASION PADANG - Rini Novita; Dilla Noviana, Husnul Wildani, Mayresti Fitria, Welta Liani, Wira Muliyani, Nur Fajar Fauzi, Febri, (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Cybersickness is an uncomfortable condition often experienced by users of virtual reality (VR) technology, which is characterized by symptoms such as dizziness, nausea and disorientation. Beat Saber, a VR-based rhythm game, has become very popular among VR users due to its engaging and interactive gameplay. Game Blink PlayStation Padang is an entertainment venue that provides VR game facilities, including Beat Saber. However, the popularity of this game is also accompanied by complaints about cybersickness experienced by players. This research aims to analyze the level of cybersickness experienced by Beat Saber players in the Game Blink PlayStation Padang as well as the factors that influence the occurrence of cybersickness. The research methodology used was a quantitative survey, with questionnaires filled out by 50 Beat Saber players. This questionnaire measures various symptoms of cybersickness experienced by players, duration of play, as well as other factors such as VR gaming experience, frequency of play, and environmental conditions of the playing area. The research results showed that the majority of respondents experienced symptoms of cybersickness with varying levels of severity. The main factors that contribute to cybersickness include playing for too long, lack of experience playing VR, and unfavorable environmental conditions such as inadequate lighting and ventilation. These findings show the importance of setting the right playing duration, gradually increasing the VR gaming experience, and optimal environmental structuring to reduce the risk of cybersickness. It is hoped that this research will provide insight for managers of VR gaming venues and players in an effort to reduce the occurrence of cybersickness and increase comfort and safety when playing VR.